Furthering fair housing : prospects for racial justice in America's neighborhoods - Steil, Justin P.; Kelly, Nicholas F., 1987-; Vale, Lawrence J., 1959-; Woluchem, Maia S., 1991- (Temple University Press, 2021)
"Examines the Department of Housing and Urban Development's 2015 Affirmatively Furthering Fair Housing (AFFH) Rule and its potential to reduce housing discrimination and promote integration in the United States"--